Ghrelin's orexigenic effect is modulated via a serotonin 2C receptor interaction - Schellekens, Harriet (2015)
Understanding the intricate pathways modulating appetite and subsequent food intake is of particular importance considering the rise in obesity incidence across the globe. The serotonergic system, specifically the 5-HT2C receptor, has shown to be of critical importance in the regulation of appetite and satiety. The GHS-R1a receptor is another key receptor wellknown for its role in the homeostatic control of food intake and energy balance. We recently showed compelling evidence for an interaction between the GHS-R1a receptor and the 5-HT2C receptor in an in vitro cell line system heterologously expressing both receptors. Here, we investigated this interaction further. First, we show that the GHS-R1a/5-HT2C dimer-induced attenuation of calcium signalling is not due to coupling to GαS, as no increase in cAMP signalling is observed. Next, flowcytometry fluorescence resonance energy transfer (fcFRET) is used to further demonstrate the direct interaction between the GHS-R1a receptor and 5-HT2C receptor. In addition, we demonstrate co-localized expression of the 5-HT2C and GHS-R1a receptor in cultured primary hypothalamic- and hippocampal rat neurons, supporting the biological relevance of a physiological interaction. Furthermore, we demonstrate that when 5-HT2C receptor signalling is blocked, ghrelin’s orexigenic effect is potentiated in vivo. In contrast, the specific 5-HT2C receptor agonist lorcaserin, recently approved for the treatment of obesity, attenuates ghrelin-induced food intake. This underscores the biological significance of our in vitro findings of 5-HT2C receptor-mediated attenuation of GHS-R1a receptor activity. Together, this study demonstrates, for the first time, that the GHS-R1a/5-HT2C receptor interaction translates into biological significant modulation of ghrelin’s orexigenic effect. This data highlights the potential development of a combined GHS-R1a and 5-HT2C receptor treatment strategy in weight management.